A Case of Calcific Myonecrosis: A Rare Clinical Presentation - Dhanasegaran Arunachalam; Balasubramaniam Ramasamy; Lalithambigai Chellamuthu (Journal of Orthopedics and Joint Surgery)
Calcific myonecrosis, a complication of late compartment syndrome, is a rare disorder characterized by peripheral calcification and central liquefaction of the entire muscle mass. We present a case of myositis ossificans impersonation that was not only unusual but also posed difficulty in diagnosis and therapeutic management. The patient was a 45-year-old man presented with right leg pain and swelling for 6 months with no constitutional symptoms. He also had a history of trauma 1 year ago. Clinically, the swelling was multilobulated, fluctuant, and tender over the mid-anterolateral aspect of right leg. Neurological examination revealed right ankle dorsiflexion and eversion of right foot. X-ray of right leg full length revealed a homogeneous radiopaque lesion over the anterior and lateral aspect. Magnetic resonance imaging (MRI) suggested a myositis ossificans lesion limited to the right leg's lateral and anterior compartments, with no hypervascularity. Routine blood tests, including liver function test, serum calcium, phosphorus, and alkaline phosphatase levels, were all normal. A nerve conduction study revealed that the right superficial and deep peroneal nerves had a lower conduction velocity. The tru-cut biopsy revealed myositis ossificans. Pus from the excision biopsy was sent for histopathological analysis, and the results revealed calcific myonecrosis. Following excision, along with physiotherapy and a course of indomethacin, patient got relieved off his symptoms and on follow-up had no signs of recurrence.